New Approach to Alternating Thickened-Unthickened Gas Flooding for Enhanced Oil Recovery - Al Hinai, N.; Saeedi, Ali; Wood, C.; Myers, M.; Valdez, R.; Xie, Sam; Jin, F. (American Chemical Society, 2018)
Direct gas thickening is a conventional mobility control method to improve volumetric sweep efficiency for miscible gas injection (MGI) projects. However, the viability of this approach with technically feasible thickeners has not been verified at the field-scale due to a combination of high costs and/or environmental issues. One approach to make this technique economically more attractive is the implementation of an alternating injection scheme (similar to water-alternating-gas (WAG)) that would require less of the thickened gas compared with a continuous injection scheme. In this study, the effectiveness of this approach where a miscible alternating injection of thickened associated gas (TAG) or thickened CO2 (TCO2) with unthickened AG is explored in both nonfractured and fractured composite carbonate cores. Twelve core-flooding experiments were conducted using different injection schemes (i.e., continuous unthickened, continuous thickened, and alternating thickened-unthickened). These tests demonstrate that overall the experimental results indicate that the alternating injection of TAG or TCO2 with unthickened AG mixture as an enhanced recovery technique may produce results similar to those with continuous thickened gas injection. This reduces the consumption of thickening agents noticeably resulting in reduced operational costs and improved economic viability for this method.